The Analysis of Cooperative Development on Economic Performance in Padang Munipacility 2012-2019 - Rano Efmon; Tan Firwan; Kamarni Neng (Pusat Pengkajian Ekonomi dan Kebijakan Publik, 2021)
This research aimed to analyze the influence of Cooperative Development on Economic Performance and Public Welfare in Padang Municipality and analyze the indirect and direct effect of Economic Performance as a mediator construct related to Cooperative Development on Public Welfare in Padang Municipality. Cooperative Performance data used in this research as panel data consists of 17 sub-sectors of Cooperative groups in Padang Municipality within 2012–2019 (8 years). Data analysis using quantitative statistical analysis approached by structural equation modeling-partial least square (SEM-PLS) method. This research found that Cooperative Development positively and significantly influenced Economic Performance and Public Welfare in Padang Municipality. Economic performance has a positive and significant influence on Public Welfare in Padang Municipality. Cooperative Development on Public Welfare through Economic Performance has a considerable contribution compared to direct influenced Cooperative Development on Public Welfare in Padang Municipality. Finally, Economic Performance has effective and complete mediation to improve Public Welfare by Cooperative Development in Padang Municipality within 2012–2019.